The Unusual Neotenic System of the Asian Dry Wood Termite, Neotermes koshunensis (Isoptera: Kalotermitidae) - Yasushi Miyaguni (Universidade Estadual de Feira de Santana, 2013)
In most lower termites, colonies are headed by neotenic reproductives of both sexes after the primary reproductives (i.e., the queen and king) are lost. The production of a neotenic sexual is inhibited by the presence of a primary reproductive of the same sex. We found an exception in the caste system of the dry wood termite Neotermes koshunensis (Kalotermitidae). The neotenic caste is exclusively male. Moreover, production of male neotenics is completely inhibited not only by the presence of a king but also by the presence of a queen. Therefore, it is likely to be difficult for N. koshunensis colonies to recover their reproductive pairs.